Refining area of occupancy to address the modifiable areal unit problem in ecology and conservation - Moat, Justin; Bachman, Steven P.; Field, Richard; Boyd, Doreen S. (Wiley, 2018)
The ‘modifiable areal unit problem’ is prevalent across many aspects of spatial analysis within ecology and conservation. The problem is particularly manifest when calculating metrics for extinction risk estimation, for example, area of occupancy (AOO).Although embedded into the International Union for the Conservation of Nature (IUCN) Red List criteria, AOO is often not used or is poorly applied. Here we evaluate new and existing methods for calculating AOO from occurrence records and present a method for determining the minimum AOO using a uniform grid. We evaluate the grid cell shape, grid origin and grid rotation with both real-world and simulated data, reviewing the effects on AOO values, and possible impacts for species already assessed on the IUCN Red List. We show that AOO can vary by up to 80% and a ratio of cells to points of 1:1.21 gives the maximum variation in the number of occupied cells. These findings potentially impact 3% of existing species on the IUCN Red List, as well as species not yet assessed. We show that a new method that combines both grid rotation and moving grid origin gives fast, robust and reproducible results and, in the majority of cases, achieves the minimum AOO. As well as reporting minimum AOO, we outline a confidence interval which should be incorporated in to existing tools that support species risk assessment. We also make further recommendations for reporting AOO and other areal measurements within ecology, leading to more robust methods for future species risk assessment.